Flexible Endoscopy: The Fundamentals - Sweigert, Patrick J.; Van Huis, Adam F.; Marcotte, Eric; Chand, Bipan (Digestive Disease Interventions, 2018)
Endoscopy highlights the intersection of technological advancements and medical application. Innovation in optics, illumination, imaging, and manufacturing has allowed for the development of a complex array of instruments for use by endoscopists. Flexible gastrointestinal (GI) endoscopy has emerged to become a well-established minimally invasive aspect of prevention, diagnosis, and treatment of GI disease.Flexible endoscopes and their associated instruments and platforms are described, acknowledging that such lists are dynamic. The procedure environment is also described in terms of location, equipment, ergonomics, personnel involved, and recovery considerations.Recommendations from GI and anesthesiology associations are outlined to summarize current practices in the administration of sedative drugs to reduce patient discomfort, allow for a technically successful procedure, and reduce patient memory of the procedure.The training process for GI endoscopy is described for general surgery residents and GI fellows. Training involves didactic and technical curriculum along with mentor-supervised endoscopic procedures. After the completion of training, residents and fellows proceed through a credentialing process, which culminates in granting privileges to an individual to perform GI endoscopic procedures. Once in practice, providers must stay up to date on the ever-changing world of medical documentation, coding, and billing to ensure appropriate reimbursement.
Keywords: gastrointestinal; endoscopy; introduction; fundamentals; training